2020
DOI: 10.5194/isprs-archives-xliv-m-1-2020-365-2020
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Analysis of Earthen Heritage Architecture as Responsive Refugee Shelters (Case Study: Domes of Northern Syria)

Abstract: Abstract. Syria has been struggling through a continuous conflict for more than nine years so far. This conflict has had a disastrous consequence, for not only Syria urban areas but also its world heritage and historical sites. Moreover, the ongoing conflict resulted in the displacement of over 13 million people that is more than half the population; including more than 6.1 million internally displaced. This long-term encampment is a growing aspect of a growing refugee crisis. The Syrian refugees have to face … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Compared with another study that has assessed the superiority of the earth technique over others [39], this study still significantly has better results in both thermal comfort (the worst result of the percentage ratio for accepted hours are 89%, 92%, and 94% in three phases respectively) and PMV (the worst result of the percentage ratio for accepted hours are 74%, 85% and 83% in three phases respectively). However, concerning CO 2 concentration, the open to yard cases (Cases 2 and 3) have better results and other cases have performed almost the same, while generally, the performances of all scenarios are between to 51%.…”
Section: Carbon Dioxide Level (Co2)mentioning
confidence: 60%
See 2 more Smart Citations
“…Compared with another study that has assessed the superiority of the earth technique over others [39], this study still significantly has better results in both thermal comfort (the worst result of the percentage ratio for accepted hours are 89%, 92%, and 94% in three phases respectively) and PMV (the worst result of the percentage ratio for accepted hours are 74%, 85% and 83% in three phases respectively). However, concerning CO 2 concentration, the open to yard cases (Cases 2 and 3) have better results and other cases have performed almost the same, while generally, the performances of all scenarios are between to 51%.…”
Section: Carbon Dioxide Level (Co2)mentioning
confidence: 60%
“…While on the other hand, regarding cooling, the same reasons and overheating in winter are evidence for the revealed approximately equal results for instance, the superior result of cooling for phase three compared to one and two. Compared with other research which has assessed the superiority of the earth technique for detached shelter zones over other humanitarian shelters [39], the three phases of this study have a significant energy saving regarding kWh/m 2 duo the attached zones pattern for a single dwelling, planning block scheme, and adopted technique (variation wall materials). Similarly, regarding energy and cost and compared with the base case scenarios in [41] with conventional materials, the bottom-up method in this study prototypes have superiority to save energy by more than 10,000 kWh in simply one case equivalent to more than 2500 USA dollars annually consequently in a camp-scale those would be vital ratios.…”
Section: Cost Implicationsmentioning
confidence: 84%
See 1 more Smart Citation
“…The simulation of vernacular dwellings is a developing research field that allows, inter alia, to obtain long-term performance predictions for a validated model, perform sensitivity and parametric analyses for improving overall performance and comfort, and examine climate change resilience and its impact on thermal comfort. In the past years, it has mainly been applied to assess thermal performance and bioclimatic strategies [22,26,[53][54][55]39,[46][47][48][49][50][51][52], thermal comfort [15,17,38,42,20,23,25,29,[32][33][34][35], energy consumption [23,55], illuminance [56], and computational fluid dynamics [57]. This section highlights the key findings stemming from the analysis of the most relevant recently published research on the simulation of vernacular dwellings for thermal performance and comfort analysis, amounting to 26 publications.…”
Section: Modelling Vernacular Dwellings: Analysis Of Researchmentioning
confidence: 99%
“…Rincon et al [22] analyzed and simulated the thermal behavior of dome shape earth-bag building in the Mediterranean climate in the same way, another study assessed the carbon impact of migrants shelters and resulted that using local materials like straw, wood, and clay, can extremely decrease the carbon footprint [8]. Ibrahim et al [23] observed the superiority of the adobe dome over other humanitarian agencies shelters as tent caravans in northern Syria through analyzed and compared based simulated research. Al Ameen [24] proposed an incremental upgrading strategy on the planning and designing phases for refugee's shelters in Iraq, for instance, a wall panel composed of layers of steel mesh, tarpaulin, and sand moreover roof canopy and sunspace.…”
Section: Introductionmentioning
confidence: 99%